CONTINUOUS IN VITRO CULTIVATION OF SPHERULES OF COCCIDIOIDES IMMITIS - Breslau, Abraham M. (1964)
Breslau, Abraham M. (Veterans Administration Center and University of California Los Angeles Center for the Health Sciences, Los Angeles, Calif.), and Mike Y. Kubota. Continuous in vitro cultivation of spherules of Coccidioides immitis. J. Bacteriol. 87:468–472. 1964.—Spherules of Coccidioides immitis were grown in vitro in continuous culture for more than 4 years. Cultures were grown in modified Converse medium in a modified Lubarsky and Plunkett culture tube incubated at 40 C under increased CO(2) tension. Spherules that had transformed from hyphae were freed from mycelial fragments, and were allowed to settle to the bottom of the tube. The mycelium which normally degenerated at 40 C was removed repeatedly with a syringe and needle until the culture was almost pure spherules. For continuous culture, 10 to 12 ml of old medium were removed, and were replaced by fresh medium previously bubbled with a mixture of 20% carbon dioxide and 80% air.